The characterisation and provenance of crude oils stranded on the South Australian coastline. Part I: Oil types and their weathering. (June 2021) - Corrick, Alexander J.; Hall, Philip A.; Gong, Se; McKirdy, David M.; Trefry, Christine; Ross, Andrew S.
Abstract: Semi-solid crude oil has been known to wash ashore along the South Australian coastline for over 120 years. The early reports pre-date offshore petroleum exploration and tanker shipping activities in Australian waters, suggesting that this stranded oil originates from natural offshore seepage. Three physically distinct varieties are represented: waxy bitumen, asphaltite and tar. In order to distinguish this natural "background" contamination of the coastline from any potential anthropogenic sources of petroleum, such as oil spills, whole-oil GC–MS analysis was employed to identify at least seven geochemically different types of stranded oil, based on a suite of 633 specimens collected from the coastline during three annual surveys of 30 ocean beaches between 2014 and 2016. The waxy bitumens, which in terms of their biomarker alkanes display an atypical pattern of alteration due to weathering in the marine environment, are more severely altered than similar specimens collected 25 years ago. Highlights: Presents a summary of physical and chemical data on 633 recent oil strandings Three varieties of semi-solid oil are represented: waxy bitumen, asphaltite, tar. Whole-oil GC–MS can separate these crude oils into seven geochemical types. The waxy bitumens display an atypical pattern of alteration due to weathering. Similar specimens collected 25 years previously are much less weathered.